Theatricality as a Critique of Modernity - Cornago, Oscar (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This essay proposes the concept of theatricality as an effective critical approach to Modernity by showing how theatricality functions and revealing the usefulness of theatricality as an instrument of analysis of the aesthetic systems and cultural discourses of the XXth century.